Pengaruh Produk Domestik Bruto, Nilai tukar dan Inflasi Terhadap Neraca Perdagangan Negara-negara di Asia Tenggara Tahun 2019-2021 - Nabila Savira; Ima Amaliah (UNISBA Press, 2023)
Abstract. Southeast Asia is the fifth highest region experiencing the world's highest cases of Covid-19 where a total of 60,560,089 people were confirmed positive and a total of 801,013 people died. This condition turned out to have an effect on economic growth in Southeast Asia which was in second place which experienced a global economic contraction due to the Covid-19 Pandemic outbreak in 2019-2021. One of the contributors to economic growth is the trade balance. The trade balance in international trade provides information on the amount of export and import values ​​that occur in a certain period. The Southeast Asia region in particular must be able to stabilize its trade balance position and be able to compete with other commodities in the international trade market. However, the value of the trade balance in Southeast Asian countries in 2019-2021 actually experienced fluctuations until it contracted negatively. Economic growth will be successful if it is supported by the level of trade balance in increasing the export of an international trade. This study aims to identify how GDP, exchange rate and inflation affect the trade balance in Southeast Asian countries and measure how much influence GDP, exchange rate and inflation have on the trade balance in Southeast Asian countries. The method used in this study is a quantitative method with data processing techniques, namely the panel data regression model and the analysis tool, namely Eviews-12. The results showed that the Gross Domestic Product variable has a positive and significant influence on the trade balance. Furthermore, the Exchange Rate variable does not have a significant effect on the trade balance. The inflation variable has a significant influence on the trade balance in Southeast Asian countries. Keywords: Covid-19 Pandemic, Trade Balance, GDP, Exchange Rate and Inflation. Abstrak. Asia Tenggara merupakan wilayah ke lima tertinggi yang mengalami kasus Covid- 19 tertinggi dunia dimana total yang terkonfirmasi positif sebesar 60.560.089 orang dan total yang meninggal sebanyak 801.013 orang. Kondisi ini ternyata berpengaruh terhadap pertumbuhan ekonomi di Asia Tenggara yang menduduki posisi ke dua yang mengalami kontraksi ekonomi global akibat wabah Pandemi Covid-19 di tahun 2019-2021. Penyumbang pertumbuhan ekonomi salah satunya adalah neraca perdagangan. Neraca perdagangan dalam perdagangan internasional memberikan informasi besarnya nilai ekspor dan nilai impor yang terjadi dalam suatu periode tertentu. Wilayah Asia Tenggara khususnya harus dapat menstabilkan posisi neraca perdagangan nya dan dapat bersaing dengan komoditas-komoditas lainnya di pasar perdagangan internasional. Namun, nilai neraca perdagangan di negara-negara Asia Tenggara pada tahun 2019-2021 justru mengalami fluktuasi sampai berkontraksi negatif. Pertumbuhan ekonomi akan berhasil apabila didukung dengan tingkat neraca perdagangan dalam peningkatan ekspor suatu perdagangan internasional. Penelitian ini bertujuan untuk mengidentifikasi bagaimana pengaruh PDB, Nilai tukar dan Inflasi terhadap neraca perdagangan di negara-negara Asia Tenggara dan mengukur berapa besar pengaruh PDB, Nilai tukar dan Inflasi terhadap neraca perdagangan di negara-negara Asia Tenggara. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan teknik pengolahan data yaitu panel data regression model serta alat analisisnya yaitu Eviews- 12. Hasil penelitian menunjukan bahwa variabel Produk Domestik Bruto memiliki pengaruh positif dan signifikan terhadap neraca perdagangan. Selanjutnya variabel Nilai Tukar tidak memiliki pengaruh yang signifikan terhadap neraca perdagangan. Variabel Inflasi memiliki pengaruh yang signifikan terhadap neraca perdagangan di negara-negara Asia Tenggara. Kata Kunci: Pandemi Covid-19, Neraca Perdagangan, PDB, Nilai Tukar dan Inflasi.